Design and properties of biomimetic irregular scaffolds for bone tissue engineering - Chen, Hao; Liu, Yang; Wang, Chenyu; Zhang, Aobo; Chen, Bingpeng; Han, Qing; Wang, Jincheng (Computers in biology and medicine, 2021)
The treatment of sizeable segmental bone defects remains a challenge encountered by surgeons. In addition to bone transplantation, porous scaffolds have become a common option. Although the mechanical and biological properties of porous scaffold have recently been the subject of intense research, pore irregularity as a critical characteristic has been poorly explored. Therefore, this study aimed to design an irregular biomimetic scaffold for use in bone tissue engineering applications. The irregular scaffold was based on the Voronoi tessellation method for similarity with the primary histomorphological indexes of bone (porosity, trabecular thickness, cortical bone thickness, and surface to volume ratio). Moreover, a new gradient method was adopted, in which porosity was maintained constant, and the strut diameter was changed to generate a gradient in the irregular scaffold. The permeability and stress concentration characteristics of the irregular scaffold were compared against three conventional scaffolds (the octet, body-centered cubic, pillar body-centered cubic). The results illustrated that the microstructure of the irregular scaffold could be controlled similarly to that of the cortical/cancellous bone unit. Simultaneously, a broad range of permeability was identified for the irregular scaffold, and gradient irregular scaffolds performed better in terms of both permeability and stress distribution than regular scaffolds. This study describes a novel method for the design of irregular scaffolds, which have good controllability and excellent permeability. •The morphology of irregular scaffold and bone unit are similar.•Relationship between scaffold parameters and characteristics are concluded.•A wide range of permeability is in irregular scaffolds.•Gradient irregular scaffold performs well in permeability and stress distribution.